Peran Dukungan Sosial terhadap Work-Family Conflict dan Employment-related Guilt Ibu Bekerja di Indonesia - Dayatri, Nyimas Fathia; Mustika, Martina Dwi (Jurnal Psikologi Udayana, 2021)
Previous studies have highlighted the importance of cultural sensitivity when investigating the work–family interface. Characteristics of each culture may impact differently on how individuals view work and family roles. This study aims to investigate whether social supports, such as spousal support, supervisory support, and domestic support, predict work–family conflict and employment-related guilt among Indonesian working married women. The study surveyed 442 women who were 23–48 years of age, employed in both the public and private sectors in Indonesia, and had at least one child at home. Path analysis was conducted to test the hypotheses. The study found that instrumental spousal support and supervisory support are significant predictors of both work-to-family conflict and family-to-work conflict. Emotional spousal support predicts family-to-work conflict but not work-to-family conflict. However, the results suggest that spousal support, supervisory support, and work-to-family conflict did not predict employment-related guilt. Domestic support also did not predict work–family conflict and employment-related guilt. The findings emphasize the importance of certain social support for employed mothers, particularly in a collectivist society like Indonesia. Organizations could provide employee assistance programs that offer counseling services to employees who have family-related problems. Training for managers and supervisors would be another approach to increasing awareness of the importance of supervisory support. Other implications of the findings and recommendations for professionals are discussed.